2000
DOI: 10.1042/bj3460063
|View full text |Cite
|
Sign up to set email alerts
|

Activation of exocytosis by cross-linking of the IgE receptor is dependent on ADP-ribosylation factor 1-regulated phospholipase D in RBL-2H3 mast cells: evidence that the mechanism of activation is via regulation of phosphatidylinositol 4,5-bisphosphate synthesis

Abstract: The physiological stimulus to exocytosis in mast cells is the cross-linking of the high-affinity IgE receptor, FcepsilonR1, with antigen. We demonstrate a novel function for ADP-ribosylation factor 1 (ARF1) in the regulation of antigen-stimulated secretion using cytosol-depleted RBL-2H3 mast cells for reconstitution of secretory responses. When antigen is used as the stimulus, ARF1 also reconstitutes phospholipase D activation. Using ethanol to divert the phosphatidic acid (the product of phospholipase D activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 51 publications
0
23
1
Order By: Relevance
“…It was shown that inhibition of PA formation resulted in decreased PIP2 synthesis and it was suggested that this lipid was required for maintaining the structural integrity and function of the Golgi. Other work has indicated a requirement for PIP2 in secretory vesicle formation (Fensome et al1996;Tfischer et al 1997;Way et al 2000). In contrast to these reports, Stamnes et al (1998) measured PA levels in Golgi membranes and found that they declined, rather than increased, during cell-free budding of coatomer-coated vesicles.…”
Section: Role In Vesicle Trafficking In Golgicontrasting
confidence: 39%
See 1 more Smart Citation
“…It was shown that inhibition of PA formation resulted in decreased PIP2 synthesis and it was suggested that this lipid was required for maintaining the structural integrity and function of the Golgi. Other work has indicated a requirement for PIP2 in secretory vesicle formation (Fensome et al1996;Tfischer et al 1997;Way et al 2000). In contrast to these reports, Stamnes et al (1998) measured PA levels in Golgi membranes and found that they declined, rather than increased, during cell-free budding of coatomer-coated vesicles.…”
Section: Role In Vesicle Trafficking In Golgicontrasting
confidence: 39%
“…Thus, secretion in mast cells, mammary epithelial cells, platelets, neutrophils and HL60 cells is inhibited by the addition of primary alcohols (Fig. 23, Stutchfield & Cockcroft 1993;Gruchalla et al 1990;Lin et al 1991;Benistant & Rubin 1990;Yuli et al 1982;Fensome et al 1996;Brown et al 1998;Siddhanta et al 2000;Way et al 2000;Boisgard & Chanat 2000). However, this could be due to changes other than inhibition of PA formation by PLD.…”
Section: Role In Exocytosis and Endocytosismentioning
confidence: 94%
“…The concentration of alcohol required to give maximal transphosphatidylation has been examined and is 0.5 -1.5 % for ethanol and 0.2-0.5% for butanol [78,79]. As a control for non-specific effects of butanol, the secondary and tertiary forms of butanol have often been employed.…”
Section: Functions Of Pldmentioning
confidence: 99%
“…The first hint that PLD activation was necessary for exocytosis in neutrophils and mast cells came from the observation that alcohols blocked exocytosis. Further analysis has confirmed the importance of ARF and PLD in exocytosis in both primary neutrophils and mast cells and in their related cell lines, HL60 cells and RBL-mast cells [64,70,73,79]. A reconstitution system has been employed to examine the requirement for ARF proteins in both PLD activation and exocytosis.…”
Section: Functions Of Pldmentioning
confidence: 99%
“…Initial study demonstrated that PIP2 and PA are critical components of exocytic machinery in mast cells and that Arf1 and Arf6 synergistically regulate PIPK5a activity [45]. Accordingly, by employing a quantitative immunofluorescence approach to follow PIP2 dynamics during mast cell exocytosis, Hammond et al demonstrated that plasma membrane PIP2 becomes transiently depleted during degranulation.…”
Section: Mast Cellsmentioning
confidence: 99%